Pengaruh Gaya Mengajar Komando Terhadap Keterampilan Passing Bawah Dalam Permainan Bola Voli Pada Peserta Didik SMP Negeri 1 Tomohon - Anatasya Jeniver Dame; Djajaty M Lolowang; Edita A Pinangkaan (STIKES Columbia Asia Medan, 2025)
The ability of students of SMP Negeri 1 Tomohon in learning physical education more specifically in mastering basic techniques in volleyball games is still a lot of students who have not been able to do underhand pass. This is because the mastery of the basic techniques of underhand pass by students given by the PE teacher turns out to be through the command style method of underhand pass material only limited to talking, orders through words. This is because the mastery of the basic techniques of underhand pass by students given by the PE teacher turns out to be through the command style method of underhand pass material only limited to talking, orders through words. The method used in this research is experimental method. The sample used was students of SMP Negeri 1 Tomohon in the academic year 2024 / 2025 totaling 30 people, which were divided into two groups, namely the experimental group with a command style totaling 15 people and a control group that did not get treatment totaling 15 people. The instrument used in this study was the “Braddy Volley Ball Test Modification. The data analysis technique used is the t-test statistical analysis technique, before the t-test is carried out. The conclusion of this study is that there is an effect of the application of command style on improving underhand pass skills in volleyball games in students of SMP Negeri 1 Tomohon.